Methyl-directed repair of frameshift mutations in heteroduplex DNA. - Dohet, C (1986)
DNA heteroduplexes with single unpaired bases of the four different kinds were prepared by annealing separated strands of bacteriophage lambda DNA and used to transfect Escherichia coli. Genetic analysis of the progeny phages obtained from transfected bacteria indicates that the E. coli mismatch repair system can recognize and repair heteroduplexes with single unpaired bases--i.e., frameshift/wild-type heteroduplexes. The repair of a particular strand of the heteroduplex is inhibited by full methylation of the adenines in the GATC sequences of that strand. Thus, it appears that the E. coli mismatch repair system can act on newly synthesized DNA strands to remove replication errors involving the insertion or deletion of a single base.